Upaya Meningkatkan Hasil Belajar Matematika Materi Bangun Datar Kelas V Memakai LKPD PMRI - Desy Priyani; Elin Riana; Elsafana Surbakti; Indri Nopianti; Kurnia Rahmadian; Linda Saputri; Saparini Saparini; Novi Lestari (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The problem found based on classroom observations was that some students did not understand the concept of flat shapes in detail. It was also found that students had not visualized the concept of flat shapes in everyday life and teachers only asked students to memorize formulas without paying attention to understanding the concept. The aim of this research is to describe the application of PMRI LKPD to improve mathematics learning outcomes, especially in flat plane material. The research carried out here is Classroom Action Research which consists of 2 cycles with 4 stages, namely the planning, implementation, observation and reflection stages. Data analysis was carried out using descriptive analysis which included calculating the average and percentage of classical completion. This research was carried out at SDN 127 Palembang, the subject of this research was class V, totaling 26 students and the object of research was the PMRI LKPD. The completeness of the learning outcomes obtained increased from cycle to cycle, namely 38% in the pre-cycle to 58% in cycle I, and reached 85% in cycle II. This shows that the use of PMRI LKPD has been proven to be able to improve mathematics learning outcomes in class V.